2003
DOI: 10.3168/jds.s0022-0302(03)73715-1
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Sialyloligosaccharides in Bovine Colostrum and Milk during the Prepartum and Early Lactation

Abstract: Sialyloligosaccharides and sialylglycoconjugates in colostrum and milk are regarded to be important biological components with respect to be source of brain gangliosides in infant and to be antiinfectional components for the attack by the pathogenic bacteria and virus. Several acidic oligosaccharides have been characterised in both bovine and human milk or colostrum. The sialyloligosaccharide content of human colostrum and milk has been extensively studied, whereas that of cows milk and colostrum has received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
128
7
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(165 citation statements)
references
References 31 publications
29
128
7
1
Order By: Relevance
“…A suitable source of 3 0 -SL might be bovine colostrum, which contains up to 1 g/l of this saccharide. 19) Of the colostrum sialyl oligosaccharides determined in this study, LSTc was present at the highest concentration. In this saccharide, Neu5Ac is linked to a nonreducing galactose in the lacto-N-neotetraose (LNnT) unit via an 2-6 linkage.…”
Section: Resultsmentioning
confidence: 99%
“…A suitable source of 3 0 -SL might be bovine colostrum, which contains up to 1 g/l of this saccharide. 19) Of the colostrum sialyl oligosaccharides determined in this study, LSTc was present at the highest concentration. In this saccharide, Neu5Ac is linked to a nonreducing galactose in the lacto-N-neotetraose (LNnT) unit via an 2-6 linkage.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the role of sialic acid in binding of Ca to ganglioside which has a great effect on the function of nervous tissue cannot be overemphasized (Schaur and Kamerling, 1997). Interestingly, one assessment of bovine colostrum and milk between prepartum and early lactation confirmed the abundance of sialyl oligosaccharides in bovine milk and suggested that bovine milk can be a potential source of sialyloligosaccharides as additives in the food or pharmaceutical industries (Nakamura et al, 2003).…”
Section: Brain Developmentmentioning
confidence: 87%
“…There is a diff erence between human and cow in the ratio of 3'-SL to 6'-SL, in that 6'-SL predominates over 3'-SL in human milk/colostrum. The levels of the acidic oligosaccharides were maximal immediately after parturition, rapidly decreasing by 48 h post-partum (Nakamura et al, 2003).…”
Section: Milk Oligosaccharides Of the Cow And Other Domestic Farm Animentioning
confidence: 95%
“…These results support the notion of anti-infl ammatory eff ects of acidic human milk oligosaccharides. Nakamura et al (2003) and Gopal & Gill (2000) stated that bovine colostrum collected immediately after parturition contains more than 1 g/L of oligosaccharides, but the mature milk contains only small amounts. Although 25 bovine oligosaccharides structures isolated from the colostrum have been completely characterized (Table 2), as many as 39 oligosaccharides have been detected using a combination of nanoelectrospray Fourier transform ion cyclotron resonance (nESI-FTICR) mass spectrometry and matrix-assisted laser desorption/ ionization Fourier transform ion cyclotron resonance (MALDI-FTICR) mass spectrometry (Tao et al, 2008).…”
Section: Immuno -Modulating Eff Ectmentioning
confidence: 99%